Twelve years a slave :authoritative text : contexts, 2013 film adaptation : criticism, reviews, interview - Northup, Solomon (A Norton critical edition, 2017)
"Twelve Years a Slave follows the life of Solomon Northup, a free blackman who was kidnapped and sold into slavery before the Civil War. Northup's memoir, published in 1853, riveted contemporary audiences but fell out of print for several generations at the start of the twentieth century. Although it was kept alive in the writings of literary scholars, historians, and bibliographers, it wouldn't return to print until 1968, and soon found a place in the canon of the literary genre known as "the slave narratives." Northup's memoir was adapted for film in 2013 by black British auteur Steve McQueen, and the film received the Oscar for "Best Motion Picture" in 2014. Readers of this critical edition will find the Editor's Preface from 1853, the 1853 edition of the text and its appendices, as well as a number of illustrations from the original publication. "Contemporary Sources (1853-1865)" offers a range of contemporary reviews and responses, an excerpt from Harriet Beecher Stowe, and coverage of the court case brought against Northup's kidnappers. "A Genealogy of Secondary Sources (1880-2014)" provides readers with a comprehensive overview of early and modern commentary on Twelve Years a Slave. "Film Criticism & Reviews: 12 Years a Slave (2013)" includes responses to the film adaptation and an interview with the director Steve McQueen. A Chronology and Selected Bibliography are also included, along with an introduction by the volume's co-authors."--Provided by publisher.